2007
DOI: 10.1007/s10518-007-9052-3
|View full text |Cite
|
Sign up to set email alerts
|

A review of research on seismic behaviour of irregular building structures since 2002

Abstract: The paper presents an overview of the progress in research regarding seismic response of plan and vertically irregular building structures. Three areas of research are surveyed. The first is the study of the effects of plan-irregularity by means of single-storey and multi-storey building models. The second area encompasses passive control as a strategy to mitigate torsional effects, by means of base isolation and other types of devices. Lastly, the third area concerns vertically irregular structures and setbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(95 citation statements)
references
References 44 publications
0
88
0
5
Order By: Relevance
“…Basu and Jain (2004) presented the definition of center of rigidity for rigid floor diaphragm buildings has been extended to unsymmetrical buildings with flexible floors. Stefano et al (2007) presents an overview of the progress in research regarding seismic response of plan and vertically irregular building structures. Dai Junw et al (2009) shown some analytical results from 3D temporal characteristics of the responses of an RC frame building subjected to both a large aftershock and the main shock of Wenchuan M s =8.0 earthquake.…”
Section: Torsionmentioning
confidence: 99%
“…Basu and Jain (2004) presented the definition of center of rigidity for rigid floor diaphragm buildings has been extended to unsymmetrical buildings with flexible floors. Stefano et al (2007) presents an overview of the progress in research regarding seismic response of plan and vertically irregular building structures. Dai Junw et al (2009) shown some analytical results from 3D temporal characteristics of the responses of an RC frame building subjected to both a large aftershock and the main shock of Wenchuan M s =8.0 earthquake.…”
Section: Torsionmentioning
confidence: 99%
“…It can be observed that Model-3 is susceptible to largest lateral displacements due to seismic forces. The reason behind this is that the discontinuous portion of the frame carries largest mass among Model [1][2][3]. On the contrary, this mass discontinuity decreases the total stiffness of the certain story level.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Stefano & Pintucchi [2] presented a review of the research on the seismic behavior of both plan and vertically irregular building structures. Tremblay and Poncet [3] examined the influence of mass irregularity for several eight-story structures with different mass discontinuity patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Some research is still under development in this field (for state-of-the-art reports, refer to Anagnostopoulos et al 2013 and to previous reviews by Rutenberg 1992Rutenberg , 2002Rutenberg and De Stefano 1997;De Stefano and Pintucchi 2008), even if the assumptions made for formulating such models involve many simplifications.…”
Section: Brief Review Of the Assessment Methods Of Induced Torsional mentioning
confidence: 99%
“…In the former case, methods considering uni-directional eccentricity, strength and ground motion were developed, subsequently improved considering these parameters in both principal directions. Concerning the multistorey models, some simplified shear-type models have been developed as well as detailed plastic hinge type models (see reviews by Rutenberg 1992Rutenberg , 2002Rutenberg and De Stefano 1997;De Stefano and Pintucchi 2008;Anagnostopoulos et al 2013).…”
Section: Brief Review Of the Assessment Methods Of Induced Torsional mentioning
confidence: 99%